Population pharmacokinetics and electrocardiographic effects of dihydroartemisinin-piperaquine in healthy volunteers - Chotsiri, P; Wattanakul, T; Hoglund, R; Hanboonkunupakarn, B; Pukrittayakamee, S; Blessborn, D; Jittamala, P; White, N; Day, N; Tarning, J (Wiley, 2017)
AIMS: The aims of the presented study were to evaluate the pharmacokinetic properties of dihydroartemisinin and piperaquine, potential drug-drug interactions with concomitant primaquine treatment, and piperaquine effects on the electrocardiogram in healthy volunteers. METHODS: Population pharmacokinetic properties of dihydroartemisinin and piperaquine were assessed in 16 in healthy Thai adults using an open-label randomized crossover study. Drug concentration-time data and electrocardiographic measurements were evaluated with nonlinear mixed-effects modelling. RESULTS: The developed models described dihydroartemisinin and piperaquine population pharmacokinetics accurately. Concomitant treatment with primaquine did not affect the pharmacokinetic properties of dihydroartemisinin or piperaquine. A linear pharmacokinetic-pharmacodynamic model described satisfactorily the relationship between the individually corrected QT-intervals and piperaquine concentrations; the population mean QT-interval increased by 4.17 ms per 100 ng/mL increase in piperaquine plasma concentration. Simulations from the final model showed that monthly and bi-monthly mass drug administration in healthy subjects would result in median maximum QT-interval prolongations of 18.9 and 16.8 ms, respectively, and would be very unlikely to result in prolongation of more than 50 ms. A single low dose of primaquine can be added safely to the existing dihydroartemisinin-piperaquine treatment in areas of multi-resistant falciparum malaria. CONCLUSIONS: Pharmacokinetic-pharmacodynamic modelling and simulation in healthy adult volunteers suggested that therapeutic doses of DHA-piperaquine in prevention or treatment are very unlikely to be associated with dangerous QT-prolongation.